2019
DOI: 10.1016/j.celrep.2019.05.092
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Metabolism Drives Histone Acetylation Landscape Transitions that Dictate Muscle Stem Cell Function

Abstract: SUMMARYThe impact of glucose metabolism on muscle regeneration remains unresolved. We identify glucose metabolism as a crucial driver of histone acetylation and myogenic cell fate. We use single-cell mass cytometry (CyTOF) and flow cytometry to characterize the histone acetylation and metabolic states of quiescent, activated, and differentiating muscle stem cells (MuSCs). We find glucose is dispensable for mitochondrial respiration in proliferating MuSCs, so that glucose becomes available for maintaining high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
118
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(126 citation statements)
references
References 75 publications
6
118
0
2
Order By: Relevance
“…Metabolism has been shown to play a crucial role in the function of many tissue resident stem cells 17 . Specifically in the context of MuSCs, recent work has shown that MuSCs display an increase in glycolytic metabolism during activation and this is important for muscle regeneration 2,3 . We similarly observed that rates of glycolysis increase during activation ( Figures 2C and 2E).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Metabolism has been shown to play a crucial role in the function of many tissue resident stem cells 17 . Specifically in the context of MuSCs, recent work has shown that MuSCs display an increase in glycolytic metabolism during activation and this is important for muscle regeneration 2,3 . We similarly observed that rates of glycolysis increase during activation ( Figures 2C and 2E).…”
Section: Discussionmentioning
confidence: 99%
“…This regenerative ability largely depends on the function of its tissue resident muscle stem cells (MuSCs), also known as satellite cells. Under homeostatic conditions, MuSCs exist in a quiescent state characterized by small size, low transcription, and low metabolic activity [1][2][3][4][5] When muscle is injured, signals from the damaged tissue environment induce MuSCs to activate, i.e. to exit the quiescent state, enter the cell cycle, and proliferate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Defective MuSC mitochondrial function results in impaired tissue regeneration 29 and MuSCs with greater mitochondrial content and oxidative phosphorylation are associated with increased capability of initiating myogenic colonies 22 . Interestingly, across tissue-specific stem cells there is increasing evidence for a link between stem cell metabolism and epigenetics 25,26,33,47 . Quiescent HSCs rely on glycolysis during selfrenewal state.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, numerous studies have identified a positive correlation between MuSC oxidative capacity and several aspects of MuSC function including cell number and muscle regenerative activity [22][23][24] . Several recent reports have delineated mechanisms that connect key tricarboxylic acid (TCA) cycle intermediates with transcriptional and epigenetic changes important for the function of MuSCs in muscle regeneration [25][26][27][28][29] . Indeed, cellular metabolism has been linked to quiescence, self-renewal, and differentiation function in other tissue-specific stem cell systems as well [30][31][32][33] .…”
Section: Introductionmentioning
confidence: 99%